HET-CAM test in evaluation of irritating action of adhesives used in shoe making industry - U.B. Lototska-Dudyk; B.P. Kuzminov; N.Ye. Chemodurova; V.A. Turkina (Medičnì Perspektivi, 2023)
The global tendency of the contemporary scientific studies is using alternative biologic models as substitutes of experimental animals. HET-CAM (The Hen's Egg Test on the Chorioallantoie Membrane Assay) is an alternative to in vivo tests involving experimental animals. This test is actively used in different biomedical studies. The aim of our work was to study the irritating potential of adhesives used in shoe making industry in experimental setting using the alternative HET-CAM method. Polyurethane, polychloroprene, rubber and styrene-butadiene adhesives that are widely used in shoe-making industry were studied . HET-CAM test was used for the evaluation of the irritating action of the aforementioned adhesives. All adhesives were applied directly onto the chorioallantoic membrane of chick embryos with reactions and changes (hemorrhages, vascular lysis and coagulation) observed and registered in 30, 120 and 300 seconds after the application of the adhesive. Irritating potential of the adhesives was evaluated according to a calculated irritating index. The most pronounced signs of irritating action were caused by polyurethane adhesives, namely hemorrhages and coagulation (30 sec) – two-component adhesive and hemorrhages (30 sec) and coagulation (120-300 sec) – one-component adhesive. Vascular reactions from application of styrene-butadiene adhesives manifested predominantly with lysis and hemorrhages (30 sec), in some samples these reactions were observed at a later time-point (120-300 sec). Irritating action of rubber adhesives manifested mostly with hemorrhages (30 sec), one observation showed lysis (120 sec). Polychloroprene adhesive caused hemorrhages (30-120 sec) and also lysis (30 sec) in one of the samples. According to the irritating index, polyurethane (one- and two-component) and styrene-butadiene adhesives were estimated to be strong irritants, while rubber and polychloroprene ones cause moderate irritating action. НЕТ-САМ test can be used as a component in the evaluation of evidence of irritating action of shoe adhesives.